Cover Image, Volume 56, Issue 4. (4th October 2018) - Pecsenye, Katalin; Tóth, Andrea; Tóth, János P.; Bereczki, Judit; Katona, Gergely; Varga, Zoltán
Abstract : The cover image is based on the Original Article Surprising diversity in the Pannonian populations of Marsh Fritillary (Euphydryas aurinia, Lepidoptera: Nymphalidae): Morphometric and molecular aspects, by Katalin Pecsenye et al., DOI:10.1111/jzs.12227 . Photo credit: Zoltán Varga.